2023
DOI: 10.54393/fbt.v3i03.57
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Mercury Complex Derived from Trimesic Acid

Javed Hussain Shah,
Shahzad Sharif,
Rashid Rehman
et al.

Abstract: The effects of mercury complexes on human body and cells vary depending on the extent of exposure and their pharmacological form. Objectives: To characterize mercury complex and then investigate the effects on cellular interaction via cell death. Methods: The synthesis of the mercury complex was carried out, and its characterization was done by FTIR, elemental percentage and powder X-ray diffraction (PXRD). The complex was analyzed through atomic force microscopy (AFM) and by microscopy imaging its surface mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…Cantoni et al, also reported that exposure of cells with HgCl2 showed fast and continuous single strand breaks in DNA and it was dependent on duration and concentration of Hg used. Toxicity of HgCl2 under equivalent exposure resulted to cell death [31]. In current work, a new mercury complex based on TMA was utilized for cellular interaction investigation and cell death.…”
mentioning
confidence: 99%
“…Cantoni et al, also reported that exposure of cells with HgCl2 showed fast and continuous single strand breaks in DNA and it was dependent on duration and concentration of Hg used. Toxicity of HgCl2 under equivalent exposure resulted to cell death [31]. In current work, a new mercury complex based on TMA was utilized for cellular interaction investigation and cell death.…”
mentioning
confidence: 99%